Student Responses to Learning Independence in Physical Education and Sports Learning at State Vocational High School 2 Mojoanyar, Mojokerto, East Java - Saputro, Arnaz Anggoro; Suharto, Johanes Paulus (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
This study was motivated by the responses of Class X students at SMKN 2 Mojoanyar to Physical Education learning due to many differences in understanding, motivation, and responses of each individual. To find out students' responses, researchers conducted research with indicators, such as internal factors, learning process, motivation, and personality. At the same time, external factors include intensity, size, opposition, repetition, movement and novelty. This research is descriptive survey research. The population amounted to 360 students. The sample taken was 72 students with the sampling technique, namely random sampling. The instrument used is a closed questionnaire, which is included in the rating scale questionnaire from its form. Using a Likert Scale score. The results of the study show the responses of class X students on Physical Education learning in the unfavourable category with a percentage (60%).